Resource utilization method for bauxite slime
By acid treatment and adding pore-forming agents and binders to bauxite sludge, the problem of difficult resource utilization of bauxite sludge is solved, efficient preparation of ceramic membrane support and high recovery rates of iron and aluminum are achieved, and environmental pollution and waste generation are avoided.
Patent Information
- Application Number
- CN202510065233.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively utilize bauxite ore mud, resulting in land occupation and environmental pollution, and the method of preparing ceramic membrane support is complicated and waste is generated.
After acid treatment of bauxite ore sludge, only pore-forming agent and binder were added to prepare the ceramic membrane support, and iron and aluminum in the acid leachate were recovered.
It realizes efficient utilization of bauxite ore mud, reduces the iron oxide content, and prepares a ceramic membrane support with good performance, with high recovery rate and no waste slag or wastewater production.
Smart Images

Figure CN119797957A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource utilization of solid waste, and in particular to a resource utilization method of bauxite sludge. Background Art
[0002] Bauxite is an aluminum ore. In the process of using bauxite to produce alumina, an industrial solid waste will be discharged. This industrial solid waste is a red clay-like substance with a high water content, called bauxite mud, also known as red mud or bauxite residue. Bauxite mud contains a large amount of clay colloids, which has the characteristics of large specific surface area, fine particles, and negative surface charge. my country produces about 80 million tons of bauxite mud every year, but the comprehensive utilization rate does not exceed 10%. Due to the inability to effectively utilize resources, the most commonly used treatment method for bauxite mud is still stockpiling. This treatment method leads to a large amount of land being occupied. At the same time, the alkaline substances in the mud gradually penetrate underground into the surrounding farmland, causing the soil to become alkaline and swampy, and the surface and groundwater sources are polluted. In addition, the particles formed by the exposed mud will be suspended in the air, polluting the atmospheric environment and causing the deterioration of the ecological environment. Therefore, it is of great significance to realize the resource utilization of bauxite mud.
[0003] At present, there are two methods for utilizing bauxite sludge: one is to extract the substances with higher value. For example, Liu (Liu J, Peng C, Jiang J, et al. Recovery of iron and aluminum from iron-rich bauxite residue by an integrated phase reconstruction approach [J]. Science of The Total Environment, 2023, 904: 166702.) et al. proposed a method consisting of alkali roasting, two-stage column leaching and carbonization decomposition for recovering aluminum and iron from iron-rich bauxite residue. However, this method is not only cumbersome, but also produces a lot of waste. The second is to utilize most of the substances in the bauxite sludge as production raw materials. For example, patent CN115974527A provides a method for preparing fly ash-red mud-based ceramic membranes, in which red mud after iron removal and high-aluminum fly ash are mixed in a ratio of (0.3-0.8):1 as raw materials to prepare ceramic membrane supports, but the added plasticizers and lubricants not only increase the preparation cost, but also introduce impurity elements.
[0004] At present, there are almost no reports on how to directly use bauxite mud to prepare a ceramic membrane support with good performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for resource utilization of bauxite sludge. The method directly removes iron from the bauxite sludge, and only adds a pore-forming agent and a binder, without adding additional plasticizers and lubricants, to prepare a ceramic membrane support body, and at the same time recovers the iron and aluminum in the acid leaching solution, thereby achieving efficient utilization of the bauxite sludge. The present invention can recover iron and aluminum in the bauxite sludge without any waste residue or wastewater, is easy to operate, has a high recovery rate, and the waste residue generated during the recovery process can be used to prepare a ceramic membrane support body with good performance, which is an ideal way to achieve resource utilization of bauxite sludge.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for resource utilization of bauxite sludge, the method comprising the following steps:
[0008] (1) adding hydrochloric acid to the ground bauxite sludge at a mass liquid-to-solid ratio of (10-20):1, and reacting for 1-5 hours at normal pressure and 80-100° C.; after the leaching reaction is completed, performing solid-liquid separation to obtain an acid leaching solution and an acid leaching residue;
[0009] The mass percentage of Fe2O3 in the acid leaching residue is 0.5% to 1%;
[0010] The concentration of the hydrochloric acid is 3-7 mol / L;
[0011] (2) mixing the acid leaching residue, the pore-forming agent and the binder uniformly, and dry-mixing for 1 to 2 hours to obtain a mixed material; then adding deionized water thereto, stirring at a constant temperature of 80 to 100° C. for 1 to 2 hours, and then covering with a plastic wrap, and aging at room temperature for 12 to 24 hours to obtain a mud material; placing the mud material in a mold, and extruding it at a pressure of 8 to 12 MPa to obtain a support body embryo;
[0012] The pore-forming agent is 5% to 25% of the mass of the mixed material; the binder is 0.5% to 2.5% of the mass of the mixed material; the amount of deionized water added is 20% to 30% of the mass of the mixed material;
[0013] The thickness of the green embryo is 2 to 3 mm.
[0014] The pore-forming agent is selected from one of starch, charcoal powder and polymethyl methacrylate (PMMA), preferably polymethyl methacrylate, and the binder is selected from methyl cellulose (Mc);
[0015] (3) heating the green support to 1200-1400° C. and sintering for 0.5-1 h to obtain a bauxite sludge-based ceramic membrane support;
[0016] The preferred sintering method is: room temperature to 300°C, at a rate of 5-10°C / min, and keeping warm for 0.5-1h; 300°C to 650°C, at a rate of 2.5-5°C / min, and keeping warm for 0.5-1h; 650°C to 1200-1400°C, at a rate of 2.5-5°C / min, and keeping warm for 0.5-1h.
[0017] The bauxite sludge composition and mass fraction include: Al2O3: 53% to 56%, Fe2O3: 31% to 34%, SiO2: 5% to 6%, TiO2: 3% to 5%, K2O: 0.5% to 1%, and Na2O: 0.1% to 0.3%.
[0018] Post-treatment of the acid leaching solution:
[0019] Sodium hydroxide is added to the acid leaching solution, and the reaction is carried out at a constant temperature of 20 to 60° C. for 2 to 5 hours. After filtration, iron hydroxide and filtrate are obtained. CO2 gas is introduced into the filtrate after the iron hydroxide is removed to obtain white aluminum hydroxide precipitate. After solid-liquid separation, aluminum hydroxide is obtained, thereby realizing the recovery of by-products iron and aluminum in the acid leaching solution.
[0020] Wherein, 4 to 12 g of sodium hydroxide is added to every 50 mL of acid leaching solution; 0.2 to 1.0 L of CO2 gas is added to every 50 mL of filtrate;
[0021] The mineral mud-based ceramic membrane support prepared by the method is used for filtering industrial wastewater.
[0022] Specifically, the steps include: filtering the industrial wastewater at 0.1MPa to 0.2MPa using a support;
[0023] The particle size of the impurities in the industrial wastewater is 1 to 100 μm;
[0024] The regeneration of the mineral mud-based ceramic membrane support body is carried out by ultrasonic cleaning.
[0025] The essential features of the present invention are:
[0026] Since the iron oxide content in bauxite mud is too high, the ceramic membrane support prepared directly as raw material will crack. In the present invention, the bauxite mud is first treated with acid to reduce the iron oxide content to less than 1% before being used as raw material to prepare the ceramic membrane support, and no cracking will occur.
[0027] Beneficial effects of the present invention:
[0028] (1) The method for removing iron from bauxite sludge provided by the present invention can reduce the mass content of iron oxide to less than 1% after iron removal, and the iron and aluminum elements in the acid leaching waste liquid can be recovered in the form of iron hydroxide and aluminum hydroxide, with a recovery rate of more than 99%.
[0029] (2) The present invention produces a bauxite sludge-based ceramic membrane support with good performance, a porosity of 31.2% to 45.1%, a flexural strength of 17.5 to 26.4 MPa, and a water flux of 6000 to 9200 L / h·m 2 MPa, which can meet the requirements of "General Technical Requirements for Porous Ceramic Products (GB / T 16533-1996)", that is, porosity ≥ 30%, flexural strength ≥ 3.5 MPa.
[0030] (3) The support can remove 99.99% of the turbidity in water and has good regeneration properties. After ultrasonic cleaning, the performance of the support is basically restored. After 10 cycles of regeneration, the performance is stable and reaches 94% of the initial value.
[0031] (4) The acid / alkali corrosion rate of the support is 1.39% / 0.52%, both of which meet the requirements of the General Technical Requirements for Porous Ceramic Products (GB / T16533-1996). That is, when the support is used in an acidic medium, the acid corrosion mass loss rate should not be greater than 2%; when used in an alkaline medium, the alkali corrosion mass loss rate should not be greater than 5%. Therefore, the support is suitable for treating acidic or alkaline solutions. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The effect of hydrochloric acid concentration on the leaching rate of iron and aluminum in the leaching reaction described in Examples 1-3;
[0033] Figure 2 The effect of reaction temperature on the leaching rate of iron and aluminum in the leaching reaction described in Examples 1 and 4-5;
[0034] Figure 3 The effect of reaction time on the leaching rate of iron and aluminum in the leaching reaction described in Examples 1 and 6-8;
[0035] Figure 4 The effect of the amount of pore-forming agent added to the support obtained in Examples 9-11 on the porosity and flexural strength of the support;
[0036] Figure 5 The effect of the amount of pore-forming agent added to the support obtained in Examples 9-11 on the water flux of the support;
[0037] Figure 6 The effect of the amount of binder added to the support obtained in Examples 9, 12-13 on the porosity and flexural strength of the support;
[0038] Figure 7 The effect of the sintering temperature of the support obtained in Examples 9, 14-15 on the water flux of the support;
[0039] Figure 8The effect of the sintering temperature of the support obtained in Examples 9, 14-15 on the acid-base corrosion rate of the support;
[0040] Fig. 9 The effect of reaction temperature on Fe precipitation rate described in Examples 16-19;
[0041] Fig.10 This is the effect of NaOH dosage on Fe precipitation rate described in Examples 16 and 20-21. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be clearly described below in conjunction with the accompanying drawings of the embodiments of the present invention.
[0043] The bauxite sludge sample disclosed by the present invention comes from Hebei Pengda New Material Technology Co., Ltd., and its specific composition is: Al2O3: 53%-56%, Fe2O3: 31%-34%, SiO2: 5%-6%, TiO2: 3%-5%, K2O: 0.5%-1%, Na2O: 0.1%-0.3%, but not limited thereto.
[0044] Example 1
[0045] This embodiment provides a method for removing iron from bauxite sludge, the method comprising the following steps:
[0046] (1) The bauxite sludge sample was ground and sieved, and then passed through a 200-mesh sieve for later use. 10 g of the sieved bauxite sludge was weighed and placed in a 250 mL three-necked flask. 5 mol / L hydrochloric acid was added to the sludge at a solid-liquid ratio of 10:1, and the acid leaching reaction was completed at 100 ° C for 4 h;
[0047] (2) After the reaction is completed, the mixture is filtered and dried, and the filter residue is subjected to X-ray fluorescence spectrometry analysis to determine the leaching rates of iron and aluminum.
[0048] Embodiment 2-8
[0049] The other steps are the same as those in Example 1, and the differences are shown in Table 1.
[0050] Table 1
[0051] Group Hydrochloric acid concentration (mol / L) Reaction temperature (oC) Reaction time (h) Example 2 3 100 4 Example 3 7 100 4 Example 4 5 80 4 Example 5 5 90 4 Example 6 5 90 1 Example 7 5 90 3 Example 8 5 90 5
[0052] from Figure 1 It can be seen that with the increase of hydrochloric acid concentration, the leaching rates of iron and aluminum increased significantly. When the hydrochloric acid concentration reached 5 mol / L, the leaching rates of iron and aluminum reached the highest and basically reached equilibrium.
[0053] from Figure 2It can be seen that with the increase of reaction temperature, the leaching rates of iron and aluminum increase significantly. When the temperature reaches 95°C, the leaching rate increases slowly with the increase of temperature. At 100°C, the leaching rate of iron is close to the maximum value, and the leaching rate of aluminum continues to increase.
[0054] from Figure 3 It can be seen that with the increase of reaction time, the reaction is more complete, and the leaching rates of iron and aluminum increase significantly. When the reaction time reaches 2h, the leaching rate of iron reaches 97.83%, and the leaching rate of aluminum reaches 55.75%. With the extension of time, from 2h to 4h, the leaching rate of iron increases slowly, and the leaching rate of aluminum increases significantly. More aluminum is leached and energy consumption increases. With the reaction time increasing to 5h, the leaching rates of iron and aluminum decrease slightly.
[0055] X-ray fluorescence spectrometry was performed on the bauxite slime and the acid leaching residue of Example 1 under the optimal acid leaching conditions. The results are shown in Table 2 (unit: wt %).
[0056] Table 2
[0057]
[0058] As shown in Table 2, after acid leaching of bauxite sludge, the mass percentage of iron oxide decreased from 32.40% to 0.75%, and a small amount of alumina was dissolved. In addition, the content of silicon dioxide increased because silicon dioxide was insoluble in hydrochloric acid and therefore concentrated in the residue. The decrease in the content of alumina and iron oxide led to a significant increase in the content of silicon dioxide.
[0059] Example 9
[0060] This embodiment provides a method for resource utilization of bauxite mud, the method comprising the following steps:
[0061] (1) The bauxite sludge after iron removal in Example 1, i.e., acid leaching residue, was used as a raw material, and the raw materials were mixed in a mass ratio of acid leaching residue: polymethyl methacrylate: methyl cellulose = 83.5%: 15%: 1.5%, and the mixture was stirred at room temperature for 2 hours to obtain a mixed material. Deionized water with a mass percentage of 20% was added to the mixed material, and the mixture was stirred at a constant temperature of 90° C. for 1 hour to further mix the sludge, and the sludge was covered with plastic wrap and aged at room temperature for 24 hours to make the water evenly distributed in the sludge;
[0062] (2) Weigh a certain mass of clay material and put it into a homemade mold, and extrude it at 10 MPa to make a support body embryo with a thickness of 2.5 mm;
[0063] (3) The support body embryo is placed in a muffle furnace and calcined to 1300°C according to a series of heating / keeping processes. The sintering method is: room temperature to 300°C, the rate is 5°C / min, and the temperature is kept for 1 hour; 300°C to 650°C, the rate is 2.5°C / min, and the temperature is kept for 1 hour; 650°C to 1300°C, the rate is 2.5°C / min, and the temperature is kept for 1 hour.
[0064] The porosity of the support prepared by the above method is 37.63%, the flexural strength is 20.1MPa, and the water flux is 7075L / h·m 2 MPa.
[0065] The porosity of the support was tested according to the Test Method for Apparent Porosity of Porous Ceramics (GB / T1966-1996), and the flexural strength of the support was tested according to the Test Method for Flexural Strength of Porous Ceramics (GB / T1965-1996). The water flux was measured by a homemade device in the laboratory.
[0066] The support of the present invention has a filtering effect on simulated industrial wastewater. In the process of treating simulated industrial wastewater with a particle size of 1 to 100 μm, the filtering pressure is 0.1 to 0.2 MPa. It can be visually observed that the treated sewage has no suspended solids and the color changes significantly. The turbidity before and after filtration is measured by a turbidity meter. The turbidity before filtration is 1196 NTU, and the turbidity after filtration is 0.06 NTU. The removal effect of turbidity reaches 99.99%. The support has good regeneration (regeneration by ultrasonic cleaning). After 10 cycles of testing, the passing performance of the support is still stable at 94% of the initial value.
[0067] Examples 10-15
[0068] The other steps are the same as those in Example 9, except for the differences shown in Table 3.
[0069] Table 3
[0070] Group Pore-forming agent addition amount (%) Binder addition amount (%) Sintering temperature (oC) Example 10 5 1.5 1300 Embodiment 11 25 1.5 1300 Example 12 15 0.5 1300 Example 13 15 2.5 1300 Embodiment 14 15 1.5 1200 Embodiment 15 15 1.5 1400
[0071] from Figure 4It can be seen that with the increase of the pore-forming agent content, the porosity gradually increases from 8.19% to 45.11%, and the flexural strength gradually decreases from 26.64MPa to 15.00MPa. The reason for this is that during the sintering process, when the temperature is low at the beginning, the melting point of PMMA is not reached. It is in a glassy state, has a certain volume, and occupies a certain position in the support. As the temperature rises, PMMA completely decomposes to produce holes, thus playing a role in pore formation. Therefore, the more pore-forming agent content there is, the more the total volume of holes inside the support increases accordingly, so the porosity increases significantly. However, the more holes there are, the easier it is to form a large number of holes that are interconnected, making the structure of the support loose, resulting in a significant decrease in flexural strength.
[0072] from Figure 5 It can be seen that as the content of the pore-forming agent increases, the water flux of the support gradually increases. The reason for this is that as the content of the pore-forming agent increases, although some of the pore size distribution will be uneven, the number and size of the holes will increase accordingly, the filtration resistance during filtration will decrease, the filtration flux will increase, and the pure water flux will also increase accordingly. In order to maintain a large porosity, pore size and water flux while making the compressive strength not too small, the amount of pore-forming agent added should not be too high or too low.
[0073] from Figure 6 It can be seen that with the increase of binder content, the porosity decreased from 31.19% to 30.27%, a small decrease, and the flexural strength increased from 19.83MPa to 21.98MPa, a small increase. Since the amount of added binder is not large, the change trend of each performance is not very obvious. The reason is analyzed to be that the binder makes the powder particles tightly bonded, increases the density of the support embryo through its own strong bonding effect, and forms a good adhesion between the support particles. With the increase of binder, the particles of the support are more tightly bonded, the porosity gradually decreases, and has better flexural strength. In order to ensure the plasticity of the support embryo and reduce the preparation cost, the amount of binder added should not be too high.
[0074] from Figure 7 It can be seen that the water flux gradually increases with the increase of sintering temperature. After reaching 1300℃, the water flux gradually decreases with the increase of sintering temperature. The reason is that when the sintering temperature is lower than 1300℃, the pore size gradually increases with the increase of sintering temperature and reaches the maximum at 1300℃; when the sintering temperature is higher than 1300℃, the densification degree of the matrix increases with the increase of sintering temperature, the pore size decreases, and the water flux keeps the same change rule with the pore size.
[0075] from Figure 8It can be seen that with the increase of sintering temperature, the acid-base corrosion rate of the support body gradually decreases. The reason is that with the increase of temperature, melting occurs between the internal particles of the support body, the pores between the particles are significantly reduced, the internal densification degree is improved, the crystal form of the raw material particles changes to form quartz (glass) and other substances to wrap the raw material, reducing the exposure degree, and the effective contact area is continuously reduced when in contact with acid and alkali solutions, so the acid-base corrosion rate shows a downward trend.
[0076] The raw materials are mixed in a ratio of acid leaching residue: polymethyl methacrylate: methyl cellulose = 72.5% to 94.5%: 5 to 25%: 0.5 to 2.5%, and sintered at 1200° C. to 1400° C. to prepare a ceramic membrane support body, the porosity of the support body is 31.2% to 45.1%, the flexural strength is 17.5 to 26.4 MPa, and the water flux is 6000 to 9200 L / h·m 2 The optimal preparation conditions are acid leaching residue: polymethyl methacrylate: methyl cellulose = 83.5%: 15%: 1.5%, sintering temperature is 1300℃, the porosity of the support is 37.63%, the flexural strength is 20.1MPa, and the water flux is 7075L / h·m 2 MPa.
[0077] Example 16
[0078] This embodiment provides a method for recovering by-products, the method comprising the following steps:
[0079] (1) 50 mL of the acid leaching solution in Example 1 was measured and 8 g of sodium hydroxide was added thereto at 50° C. to convert all the iron in the solution into iron hydroxide, followed by solid-liquid separation, and the iron hydroxide precipitate was collected to achieve iron recovery;
[0080] (2) The filtrate after removing the iron hydroxide is collected and 0.5L CO2 is introduced into it to obtain a white aluminum hydroxide precipitate. After solid-liquid separation, aluminum can be recovered.
[0081] Examples 17-21
[0082] The other steps are the same as those in Example 16, except for the differences shown in Table 4.
[0083] Table 4
[0084] Group Reaction temperature (oC) NaOH dosage (g) Embodiment 17 20 8 Embodiment 18 40 8 Embodiment 19 60 8 Embodiment 20 50 4 Embodiment 21 50 10
[0085] from Fig. 9 It can be seen that with the increase of temperature, Fe 3+The concentration of iron gradually decreases and the precipitation rate gradually increases. When the reaction temperature rises to 50°C, the iron is basically precipitated completely. At this time, further increasing the temperature will only increase unnecessary energy consumption. Therefore, the optimal reaction temperature is 50°C.
[0086] from Fig.10 It can be seen that as the amount of sodium hydroxide added increases from 4g to 8g, the concentration of iron in the solution gradually decreases from 15.8g / L to close to 0g / L. When the amount of sodium hydroxide added is 8g, the iron has been basically precipitated completely. Therefore, with the continued addition of sodium hydroxide, the iron concentration remains basically unchanged, proving that the iron has been completely converted into ferric hydroxide. Therefore, the amount of sodium hydroxide added is 8g for every 50mL of acid leaching solution treated.
[0087] From the above, it can be seen that the method for resource utilization of bauxite mud provided by the present invention not only overcomes the problem of improper waste dumping, but also can recycle iron and aluminum, and at the same time provides a low-cost method for preparing ceramic membrane supports, which is in line with the requirements of the green, low-carbon circular economy strategy.
[0088] The several specific embodiments of the present invention disclosed above are only used to help explain the present invention. Obviously, the described embodiments are only part of the specific embodiments of the present invention, and the present invention is not limited to the above embodiments. Any modification, replacement, improvement, etc. made by ordinary technicians in this field without departing from the scope of the present invention are within the protection scope of the present invention.
[0089] Matters not covered by the present invention are known technologies.
Claims
1. A method for resource utilization of bauxite sludge, characterized in that: The method comprises the following steps: (1) adding hydrochloric acid to the ground bauxite sludge at a mass liquid-to-solid ratio of (10-20):1, and reacting for 1-5 hours at normal pressure and 80-100° C.; after the leaching reaction is completed, performing solid-liquid separation to obtain an acid leaching solution and an acid leaching residue; The mass percentage of Fe2O3 in the obtained acid leaching residue is 0.5% to 1%; (2) mixing the acid leaching residue, the pore-forming agent and the binder uniformly, and dry-mixing for 1 to 2 hours to obtain a mixed material; then adding deionized water thereto, stirring at a constant temperature of 80 to 100° C. for 1 to 2 hours, and then covering with a plastic wrap, and aging at room temperature for 12 to 24 hours to obtain a mud material; placing the mud material in a mold, and extruding it at a pressure of 8 to 12 MPa to obtain a support body embryo; The pore-forming agent is 5% to 25% of the mass of the mixed material; the binder is 0.5% to 2.5% of the mass of the mixed material; the amount of deionized water added is 20% to 30% of the mass of the mixed material; (3) The green support body is heated to 1200-1400° C. and sintered for 0.5-1 h to obtain a bauxite sludge-based ceramic membrane support body.
2. The method for resource utilization of bauxite mud according to claim 1, characterized in that: The concentration of the hydrochloric acid is 3-7 mol / L.
3. The method for resource utilization of bauxite mud according to claim 1, characterized in that: The sintering method is: room temperature to 300°C, at a rate of 5-10°C / min, and keeping warm for 0.5-1h; 300°C to 650°C, at a rate of 2.5-5°C / min, and keeping warm for 0.5-1h; 650°C to 1200-1400°C, at a rate of 2.5-5°C / min, and keeping warm for 0.5-1h.
4. The method for resource utilization of bauxite mud according to claim 1, characterized in that: The bauxite sludge composition and mass fraction include: Al2O3: 53% to 56%, Fe2O3: 31% to 34%, SiO2: 5% to 6%, TiO2: 3% to 5%, K2O: 0.5% to 1%, and Na2O: 0.1% to 0.3%.
5. The method for resource utilization of bauxite mud according to claim 1, characterized in that: The pore-forming agent is one of starch, charcoal powder and polymethyl methacrylate (PMMA), and the binder is methyl cellulose (Mc).
6. The method for resource utilization of bauxite mud according to claim 1, characterized in that: The thickness of the green embryo is 2-3 mm.
7. The method for resource utilization of bauxite mud according to claim 1, characterized in that: Post-treatment of the acid leaching solution: Sodium hydroxide is added to the acid leaching solution, and the reaction is carried out at a constant temperature of 20 to 60° C. for 2 to 5 hours. After filtration, iron hydroxide and filtrate are obtained. CO2 gas is introduced into the filtrate after the iron hydroxide is removed to obtain white aluminum hydroxide precipitate. After solid-liquid separation, aluminum hydroxide is obtained, thereby realizing the recovery of by-products iron and aluminum in the acid leaching solution. Among them, 4 to 12 g of sodium hydroxide is added to every 50 mL of acid leaching solution; and 0.2 to 1.0 L of CO2 gas is added to every 50 mL of filtrate.
8. The use of the mineral mud-based ceramic membrane support prepared by the method of claim 1, characterized in that: Used for industrial wastewater filtration.
9. The application method according to claim 8, characterized in that it comprises the following steps: filtering the industrial wastewater at 0.1 MPa to 0.2 MPa using a support; The particle size of the impurities in the industrial wastewater is 1 to 100 μm.
10. The application method according to claim 9, characterized in that: The regeneration of the mineral mud-based ceramic membrane support body is carried out by ultrasonic cleaning.